Using Clinical Cases to Restore Basic Science Immunology Knowledge in Physicians and Senior Medical Students - Karim, Mohammed Yousuf (Frontiers in Immunology, 2020)
The majority of medical students and many physicians find basic science Immunology confusing and the teaching of Immunology to be uninteresting. Physicians undergoing training in a range of disciplines treat patients with immunological disease, including Allergy/Immunology and Rheumatology. It is essential for senior medical students and physicians to understand the pathology of immune diseases and the pharmacology of immune interventions. In order to optimise this learning, underlying concepts of basic Immunology need to be revised, or sometimes learnt for the first time. Teachers may need to overcome baseline attitudinal negativity. Medical students and postgraduates are more able to relate to basic Immunology if approached through a clinical route. Case presentations and case-based discussions are a familiar format for medical students and physicians, though typically they are utilised to enhance understanding of clinical presentation, investigation, and treatment. Hence, they may be more receptive to “difficult” Immunology concepts when presented in a familiar teaching framework. Although there is data supporting case-based learning for basic Immunology in medical students, there is little data in physicians. Extrapolating from the medical student literature, I devised a programme of clinical cases for physicians whereby understanding the immunopathological basis of the condition and/or its immunological treatment was employed as a platform to appreciate the basic science Immunology in more depth. A variety of cases were selected to illustrate different immunological topics. The sessions were small group, and highly interactive in nature. As this programme has only recently been introduced, formal evaluation has yet to be concluded.